Psychosocial factors influencing quality of life in patients with primary brain tumors in Pakistan: an analytical cross-sectional study - Nida Zahid; Russell Seth Martins; Nick Brown; Wajeeha Zahid; Iqbal Azam; Aneesa Hassan; Khabir Ahmad; Shireen Shehzad Bhamani; Adnan Abdul Jabbar; Nargis Asad; Muhammad Shahzad Shamim; Rashid Jooma Khan; et al. (BMC Research Notes, 2023)
Abstract Objective Despite quality of life (QoL) being recognized as an important outcome in neuro-oncology, there is a lack of research from Pakistan where sociocultural differences may influence QoL. This study aimed to measure the QoL in patients with primary brain tumors (PBTs) and assess its association with mental health outcomes and social support. Results Our study included a total of 250 patients, with a median age of 42 years (range 33–54 years). The commonest brain tumors were glioma (46.8%) and meningioma (21.2). The mean global QoL of the sample was 75.73 ± 14.9. The majority of patients had high social support (97.6%) and were not depressed (90%) or anxious (91.6%). On multivariable linear regression, global QoL was inversely associated with no or low income (beta coefficients: −8.75 to −11.84), having hypertension (−5.53), currently using a urine catheter (−13.55), having low social support (−28.16) suffering from mild (−15.31) or symptomatic (−23.84) depression, or mild anxiety (−13.22).